Circulating PGRN Levels Are Increased but Not Associated with Insulin Sensitivity or β-Cell Function in Chinese Obese Children. (29th July 2018) - Wang, Fengyun; Chen, Ting; Sun, Ling; Lv, Haitao; Li, Xuan; Shen, Jie; Chen, Linqi; Chu, Zhenyu; Hou, Miao
Abstract : Progranulin (PGRN), a novel peptide that has recently emerged as an important regulatory adipokine, is relevant to energy homeostasis and obesity in animals and adult humans. Little is known about its roles in children. The aim of the current study was to determine the potential role of PGRN and explore its relationship to various obesity-related markers in obese children. This was a cross-sectional study composed of 77 children (43 obese and 34 healthy, age 8.68 ± 0.28 and 8.46 ± 0.45 years, resp.). The PGRN levels were significantly higher in obese children (102.44 ± 4.18 ng/mL) comparing to controls (69.32 ± 5.49 ng/mL) (P < 0.05 ). Moreover, the PGRN levels were positively correlated with triglyceride (TG), total cholesterol (TC), IL-6, systolic blood pressure (SBP), and diastolic blood pressure (DBP) in obese children after adjusted for BMI and age. However, there was no correlation of serum PGRN levels with OGTT-derived dynamic parameters, HOMA-IR, or HOMA- β in obese children. The results suggest that serum PGRN levels are significantly higher in obese children in China and correlate significantly with obesity-related markers. Increased PGRN levels may be involved in the pathological mechanism of childhood obesity.